Can cognitive insight predict symptom remission in a first episode psychosis cohort?. Issue 1 (December 2017) - O'Connor, Jennifer; Ellett, Lyn; Ajnakina, Olesya; Schoeler, Tabea; Kollliakou, Anna; Trotta, Antonella; Wiffen, Benjamin; Falcone, Aurora; Di Forti, Marta; Murray, Robin; Bhattacharyya, Sagnik; David, Anthony
Abstract Background The outcome of first episode psychosis (FEP) is highly variable and difficult to predict. Cognitive insight measured at illness onset has previously been found to predict psychopathology 12-months later. The aims of this study were to examine whether the prospective relationship between cognitive insight and symptom severity is evident at four-years following FEP and to examine some psychological correlates of cognitive insight. Methods FEP participants (n = 90) completed the Beck Cognitive Insight Scale (BCIS) at illness onset, and associations between BCIS scores with symptom severity outcomes (4-years after FEP) were assessed. The BCIS scales (self-reflectiveness andself-certainty ) were examined as a composite score, and individually compared to other cognitive measures (IQ and jumping to conclusions (JTC) bias). Results Regression analyses revealed that the cognitive insight composite did not predict 4-year symptom remission in this study while the self-reflection subscale of the BCIS predicted severity of symptoms at 4-years. Self-certainty items of the BCIS were not associated with symptom severity. Significant correlations between the JTC bias, self-certainty and IQ were found, but self-reflection did not correlate with these other cognitive measures. Conclusions Self-reflective capacity is a more relevant and independent cognitive construct than self-certainty for predicting prospective symptom severity in psychosis. Improving self-reflection may be a useful target for early intervention research.